MEDICINAL EFFICACY OF EDIBLE MACRO FUNGUS Ganoderma Ganoderma applanatum (PERS.) PAT. – A REVIEW - SUKUMAR DANDAPAT; MANOJ KUMAR; ROHIT SRIVASTAVA; MANORANJAN PRASAD SINHA (The Bioscan, 2022)
Medicinal mushrooms are used in traditional medication. They are easily available and cost effective source for the people of rural and tribal areas. In the present review, an attempt has been made to congregate the taxonomic, mycochemical and pharmacological studies done on an important medicinal mushroomGanoderma applanatum. Extensive experimental studies prove that Ganoderma applanatum possesses antibacterial, antifungal, antiviral, antioxidant, anticancer, anticholestromic, antidiabetic, nephroprotective, hepatoprotective, hypouricemic, immunostimulatory properties, which help it to play role in prevention and treatment of many disease. Therefore, it is worthwhile to review therapeutic properties of G. applanatum to give an overview of its status to scientist both modern and ancient.